2022
DOI: 10.26480/asm.02.2022.48.54
|View full text |Cite
|
Sign up to set email alerts
|

Insights of Caste Determinations in Social Insects

Abstract: Eusocial insects display caste structures in which reproductive ability is possessed by a single or a few queens while all other colony members act as workers. In social insects like ants, bees, and termites, vital physiological processes are regulated at the colony scale. Females in social insects have at least one reproductive caste and one nonreproductive caste; many termites have at least two male castes. The castes have considerable anatomical, physiological, and behavioural differences in higher social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The existence of broad peaks indicates that the crystalline structures of WB (Figure S1) have disappeared after carbonization and activation, which are reflected in the amorphous domain. [37] The WB-AC with large dspacing comparable with WB-RC proves that small primary mesopore sizes and considerable amounts of micropores. Moreover, the peak at 42°in WB-RC completely disappeared, and the relative intensity for the peak at 21°is slightly weaker than the WB-AC.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The existence of broad peaks indicates that the crystalline structures of WB (Figure S1) have disappeared after carbonization and activation, which are reflected in the amorphous domain. [37] The WB-AC with large dspacing comparable with WB-RC proves that small primary mesopore sizes and considerable amounts of micropores. Moreover, the peak at 42°in WB-RC completely disappeared, and the relative intensity for the peak at 21°is slightly weaker than the WB-AC.…”
Section: Resultsmentioning
confidence: 88%
“…It is clearly observed that both the materials displayed a diffused curve lacking significant peak intensity around 23° and 42°, corresponding to the (002) and (100) crystal planes, respectively. The existence of broad peaks indicates that the crystalline structures of WB (Figure S1) have disappeared after carbonization and activation, which are reflected in the amorphous domain [37] . The WB‐AC with large d‐spacing comparable with WB‐RC proves that small primary mesopore sizes and considerable amounts of micropores.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in solitary species, juvenile hormone delays moulting and pupation, and combined with sufficient nutrition, leads to larger adult body size [30]. Various studies have shown that juvenile hormone III, the most common form of juvenile hormone in social Hymenoptera [31], affects adult size and morphology in ants [7,22,27,32,33]. In the ant Harpegnathos saltator, treating larvae with juvenile hormone increases their likelihood of developing into larger adults or into queens [33].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins that make up these jellies are synthesized by nurse workers who feed the larvae [19] and adapt quantitatively and qualitatively the composition of their jelly diet [17,20]. Although there is evidence for a role for nutrition in caste determination in social insects other than in honeybees [11,12,18,[21][22][23][24], the molecular and social mechanisms of caste fate determination and adult body size are far less understood.…”
Section: Introductionmentioning
confidence: 99%